Historical statements and concepts as constitutive elements of historical reality - Mishalova, Olena (Actual Problems of Mind, 2017)
The paper deals with an issue of the semiotic nature of historical reality, it is substantiated the point that historical statements and concepts are constitutive elements of historical reality. It is stressed that values are an integral part of historical knowledge therefore the author attempts to outline her own concept of the objectivity of historical knowledge.